H. T. Klami, Julius Paulus. Lakinussura 200 — Luvun Roomassa - Kodrębski, Jan (Czasopismo Prawno-Historyczne, 1979)
Recenzja: Hannu Tapani Klami, Julius Paulus. Lakinussura 200 — Luvun Roomassa, Vammala 1975, ss. 103.